Excessive Daytime Sleepiness in Major Dementia Syndromes. Issue 4 (June 2019) - Boeve, Angelica; Ferman, Tanis J.; Aakre, Jeremiah; St. Louis, Erik; Silber, Michael; Machulda, Mary; Fields, Julie; Graff-Radford, Neill; Mielke, Michelle; Geda, Yonas; Jones, David; Graff-Radford, Jonathon; et al.
There has been no comparison of excessive daytime sleepiness (EDS) in patients with Alzheimer's disease dementia (AD), dementia with Lewy bodies (DLB), and behavioral variant frontotemporal dementia (bvFTD). We identified patients with mild dementia who met criteria for these disorders who also had the Epworth Sleepiness Scale (ESS) completed. The sample included 17 bvFTD, 111 AD, and 31 DLB. An ESS score ≥10 was considered abnormal and consistent with EDS. Analyses with age and sex as covariates revealed higher mean ESS scores for DLB compared to the other groups (DLB 13.9 [5], bvFTD 9.6 [8], AD 8.8 [5], P < .05). An ESS score ≥10 was significantly more likely to occur in DLB compared to bvFTD or AD (DLB 81% vs bvFTD 47% vs AD 45%, P < .01). In patients with mild dementia, EDS is greatest in DLB and comparably lower in bvFTD and AD.